Molecular and Serological Testing for Brucellosis in Egypt - Johar, Dina; Elaal, Mahmoud A.M. Abd; Bakr, Asmaa; Sakr, Rokia A.; Bahbah, Eshak I.; Elshemy, Eman Elsayed; Zaky, Samy (The International Journal of Gastroenterology and Hepatology Diseases, 2022)
Background Brucellosis is highly endemic in the Mediterranean Basin, including Egypt. Despite attempts to control the disease in Egypt, there are still significant problems with diagnostic accuracy. The prevalence and incidence of Brucellosis are unknown and we have uncertain predictive prognostic tests for Brucellosis treatment results. Identification of the actual epidemiological burden of Brucellosis in Egypt, and levels of the Brucellosis antibody titer among rural and urban populations is critical to the evaluation of combined treatment approaches that achieve lesser relapse rates. Objective To determine the current prevalence of Brucellosis infections in Egypt and changes in its epidemiological pattern. Methods We compared the available diagnostic yield, sensitivity, specificity, accuracy, cost, and time consumption of serological tests with those from quantitative polymerase chain reaction (qPCR) to establish their ability to meet the diagnostic criteria. Also, we conducted surveillance of the rates of Brucellosis infection in both humans and animals. Results The enzyme-linked immunosorbent assay (ELISA) and blood cultures were less sensitive diagnostic methods for the detection of Brucellosis. These approaches are technically challenging and have a high likelihood of false negatives. Therefore, they are best reserved for suspected cases with negative standard agglutination test (SAT). Conclusion A more practical approach to the diagnosis of Brucellosis depends on epidemiological testing for risk factors, clinically suspected cases, and SAT titers ≥ 1/320. Strategies to prevent relapsing include: 1) Health education of patients, 2) Long-term triple therapy, e.g., three months, with possible extension to six months in severe or recurrent cases or when complications occur.
Keywords: Brucellosis